Analisis Perlindungan Hak Pelaku Tindak Pidana Anak Dalam UU No. 11 Tahun 2012 Perspektif Teori Keadilan John Rawls - Ahmad Wildan Rofrofil Akmal; Erik Wibowo (Yayasan Cendekia Gagayunan Indonesia, 2025)
Criminal acts committed by children are increasingly frequent in Indonesia. The state is responsible for providing special protection for their rights. Law No. 11 of 2012 on the Juvenile Criminal Justice System was introduced as a state response to the need for a child-friendly justice system. This research aims to analyze the legal protection of children who commit criminal acts from the perspective of John Rawls' theory of justice. This study employs a normative legal method using statutory and conceptual approaches. Data sources were obtained through literature studies using primary and secondary legal materials such as legislation, academic literature, and journals. Law No. 11 of 2012 provides legal protection for child offenders through diversion mechanisms and the application of restorative justice. These measures are taken to avoid the imprisonment of children, protect their fundamental rights, and ensure a humane and educational judicial process. The government also emphasizes the involvement of the community and families in the child’s recovery process. The protection of children under Law No. 11 of 2012 aligns with the two main principles of John Rawls' theory of justice: the principle of equal liberty and the difference principle. Children, as a vulnerable group, are positioned as individuals whose rights must be guaranteed equally with other children and who must receive special treatment to ensure substantive justice. This law reflects a legal partiality toward children as the most disadvantaged group within the criminal justice system.